Anesthesia Management in a Hypertrophic Cardiomyopathy Patient with Brain Tumor: A Case Report: Anesthesia in a hypertrophic cardiomyopathy patient with brain tumor - Azizi Farsani, Hamidreza; Asgari, Sogol; Behnaz, Faranak (Novelty in Biomedicine, 2021)
Background: Brain tumour surgeries are high-risk because of their potential for postoperative fetal complications. This risk is exaggerated in the presence of hypertrophic cardiomyopathy (HCM). Hypertrophic cardiomyopathy includes asymmetric left ventricular hypertrophy with mitral valve dysfunction that obstructs the left ventricular outflow tract. Various postoperative factors may accelerate this obstruction and lead to life-threatening consequences. Hypertrophic obstructive cardiomyopathy (HOCM) is a type of HCM that obstructs the left ventricular outflow tract. The most important parameters are preload, afterload, and ventricular contraction, resulting from the surgical method, anesthesia factors, and changes in intravascular volume that are prone to fluctuations in HOCM patients in the postoperative period. These cases increase the risk of arrhythmias and myocardial ischemia and significantly increase patients’ morbidity and mortality after surgery. It should avoid lowering blood pressure, increasing heart rate, and reducing preload and afterload in these patients. Cases Report: In this study, we reported a 59 years old man who complained of a speech disorder that had worsened three months ago and mentioned a history of hypertrophic cardiomyopathy. The patient underwent brain tumor surgery and was discharged from the hospital with proper management of anesthesia. Conclusion: Loading and maintaining sinus rhythm are recommended to prevent complications. We presented the intraoperative management of a patient with HCM undergoing a brain tumour resection and discussed its complications.